2010
DOI: 10.1126/science.1189862
|View full text |Cite
|
Sign up to set email alerts
|

MiR-33 Contributes to the Regulation of Cholesterol Homeostasis

Abstract: Cholesterol metabolism is tightly regulated at the cellular level. Here we show that miR-33, an intronic microRNA (miRNA) located within the gene encoding sterol-regulatory element–binding factor–2 (SREBF-2), a transcriptional regulator of cholesterol synthesis, modulates the expression of genes involved in cellular cholesterol transport. In mouse and human cells, miR-33 inhibits the expression of the adenosine triphosphate–binding cassette (ABC) transporter, ABCA1, thereby attenuating cholesterol efflux to ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

36
1,155
3
22

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,114 publications
(1,216 citation statements)
references
References 17 publications
36
1,155
3
22
Order By: Relevance
“…These findings support our previous study that demonstrated that miR-223 targets SR-BI's 3′ UTR (41), and a recent study that reported that miR-223 regulates SR-BI in HepG2 cells (42). Hepatic miR-223 levels were found to be equal to or greater than other miRNAs that have been demonstrated to be physiologically relevant in the liver (18), and miR-223 inhibition was found to significantly increase SR-BI (SCARB1), HMGCS1, and SP3 mRNA levels, and significantly increase HDL-C uptake in Huh7 cells. In parallel to these direct effects, miR-223 was also found to have an indirect effect on cholesterol efflux because ABCA1 expression and function were found to be linked to intracellular miR-223 levels through the Sp3 TF.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…These findings support our previous study that demonstrated that miR-223 targets SR-BI's 3′ UTR (41), and a recent study that reported that miR-223 regulates SR-BI in HepG2 cells (42). Hepatic miR-223 levels were found to be equal to or greater than other miRNAs that have been demonstrated to be physiologically relevant in the liver (18), and miR-223 inhibition was found to significantly increase SR-BI (SCARB1), HMGCS1, and SP3 mRNA levels, and significantly increase HDL-C uptake in Huh7 cells. In parallel to these direct effects, miR-223 was also found to have an indirect effect on cholesterol efflux because ABCA1 expression and function were found to be linked to intracellular miR-223 levels through the Sp3 TF.…”
Section: Discussionsupporting
confidence: 81%
“…In summary, we have described a small, but powerful regulator of metabolism because miR-223 likely coordinates cholesterol homeostasis through multiple direct and indirect mechanisms controlling cholesterol biosynthesis, uptake, and efflux. Results from this and other recent studies on miRNAs (13,18) highlight the potential importance of miRNAs in the etiology of dyslipidemias and cardiovascular disease. As such, miR-223 has great potential as a therapeutic target to control systemic cholesterol levels in the prevention and treatment of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While this manuscript was under revision, two independent laboratories reported similar findings (38,39).…”
Section: Methodsmentioning
confidence: 55%